Media, Cultural Consumption and Support for Democracy in Post-Revolutionary Egypt. (October 2016) - Hassan, Mazen; Kendall, Elisabeth; Whitefield, Stephen
While much of the commentary about the Arab Spring, and the Egyptian revolution in particular, points to the importance of new social media and engagement with literary genres in generating support for democracy, the comparative literature remains ambivalent on this question. The aim of this article is to put the connection between cultural consumption of various sorts and democratic support to a rigorous test using data from a survey conducted by the authors in 2012 after the first parliamentary elections in Egypt after the revolution. The research design involves a hard test, in which we estimate the significance of cultural consumption after controlling for a broad range of 'usual suspects' affecting democratic attitudes. The results show positive effects for new social media on support for democracy, but little or no effect for literary genres.